Riotous Robots / Totally - Goldsmith, Mike Dr.; Philip, Mike (London : Scholastic, 2003)
Riotous Robots are taking over the world. From underwater discovery to space travel, these metallic marvels are getting the most exciting jobs on the planet. This cybernetic guide tells you how they're doing it. It helps to discover a robot that's forced to snack on slugs for a living and a robo-alligator that works as a scarecrow.
Keywords: Riotous Robots; Technology; Robotics